The Ballad of Ben and Stella Mae : Great Plains Outlaws Who Became FBI Public Enemies Nos. 1 and 2 - Cecil, Matthew (Book collections on Project MUSE., 2017)
"Tragic tale of Topeka natives Ben Dickson (1912-1939) and Stella Mae Redenbaugh Dickson (1922-1995), Depression Era lovers/spouses on the lam from the law, accused of bank robbery and kidnapping, tabbed Public Enemies Nos. 1 and 2 by the FBI, pursued by law enforcement forces much more violent and brutal than themselves, and victimized by an FBI that inflated their notoriety, created a false account of Ben''s death to bolster the Bureau's crime-fighting image, and pushed for maximum punishment for Stella Mae"--